Aspects of the pathology of money: monetary essays from four decades - Heilperin, Michael Angelo (London: published by Joseph for the Graduate Institute of International Studies, Geneva, 1968)
The book contains essays concemed primarily with the theoretical properties of a well-functioning intemational monetary system, which must be judged not by the standards of present textbooks but in light of the state of knowledge at the time the essays were written. It also provides a significant clue to the development on intemational monetary order. It highlights the experience of post-World War I inflations and as a mature scholar he analyzed their causes and consequences.
Includes bibliographic footnotes
usc 08/11/18
Loans
Keywords: International finance